Pembangunan Ekonomi Berbasis Blue Economy Pada Pariwisata Bali - Diputra, Gde Indra Surya; Kawiana, I Gede Putu; Pratiwi, Komang Ary; Saraswathi, Ida Ayu Anggawulan (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This project aims to investigate Blue Economy-Based Economic Development within Bali's tourism sector. This study employs a systematic review design, specifically a literature review that evaluates high-quality journals filtered by inclusion criteria, employing databases such as Google Scholar, Science Direct, and ResearchGate for its research. A search of papers from 2017 to 2024 yielded 142 results pertaining to the phrase "Blue Economy" in relation to Bali Tourism, which were categorized into 20 journals based on thematic relevance and subsequently examined. The study's findings indicate that Blue Economy-oriented economic development in Bali's tourism industry provides a sustainable method for utilizing marine resources to enhance economic welfare while preserving the environment. This strategy improves the tourism industry by incorporating efficiency, innovation, and sustainability via marine ecotourism, marine conservation, renewable energy, and circular economy practices within the marine sector.